2005
DOI: 10.1186/1477-7827-3-53
|View full text |Cite
|
Sign up to set email alerts
|

Potential targets of transforming growth factor-beta1 during inhibition of oocyte maturation in zebrafish

Abstract: Background: TGF-beta is a multifunctional growth factor involved in regulating a variety of cellular activities. Unlike mammals, the function of TGF-beta in the reproduction of lower vertebrates, such as fish, is not clear. Recently, we showed that TGF-beta1 inhibits gonadotropinand 17alpha, 20beta-dihydroxyprogesterone (DHP)-induced maturation in zebrafish. The aim of the present study was to investigate the mechanisms underlying this action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…For example, double conditional knockout of Smad2 and Smad3, which are two TGFβ major signaling components, leads to severe fertility and fecundity defects in mice, supporting the involvement of an intraovarian Smad2/3 pathway in mediating oocyte-produced signals essential for coordinating key events of the ovulatory process (Pangas and Matzuk, 2004). Similarly, recent findings suggest that TGFβ may play a role in preventing premature oocyte maturation in zebrafish by down-regulating basal and human chorionic gonadotropin-induced 20β-hydroxysteroid dehydrogenase, the luteinizing hormone receptor, and membrane progestin receptor-β mRNA levels (Kohli et al, 2005). Our results have shown that the kinase activity of TβRII is required for zkm23 phosphorylation, and that blockade of zkm23 results in an inhibition of transcriptional activation induced by TGFβ, suggesting that zkm23 is an important TGFβ signaling intermediate in zOFCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, double conditional knockout of Smad2 and Smad3, which are two TGFβ major signaling components, leads to severe fertility and fecundity defects in mice, supporting the involvement of an intraovarian Smad2/3 pathway in mediating oocyte-produced signals essential for coordinating key events of the ovulatory process (Pangas and Matzuk, 2004). Similarly, recent findings suggest that TGFβ may play a role in preventing premature oocyte maturation in zebrafish by down-regulating basal and human chorionic gonadotropin-induced 20β-hydroxysteroid dehydrogenase, the luteinizing hormone receptor, and membrane progestin receptor-β mRNA levels (Kohli et al, 2005). Our results have shown that the kinase activity of TβRII is required for zkm23 phosphorylation, and that blockade of zkm23 results in an inhibition of transcriptional activation induced by TGFβ, suggesting that zkm23 is an important TGFβ signaling intermediate in zOFCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is evidence for the presence of the major TGFβ signaling pathway molecules in the fish ovary (Calp et al, 2003; Dick et al, 2000; Hardie et al, 1998; Kohli et al, 2005; Kohli et al, 2003). Further, TGFβ sumperfamily members (TGFβ, Activin, Inhibin, GDF9, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In human, miR-202-5p levels in follicular fluid are positively correlated with the fertilization potential of oocytes (41), suggesting a role for miR-202-5p in the proper development of oocytes. Moreover, miR-202-5p has been shown to regulate PI3K (42) and TGF-β signaling, both of which play important roles in folliculogenesis and oocyte maturation (43, 44).…”
Section: Discussionmentioning
confidence: 99%
“…Although in lower vertebrates there is no direct evidence to firmly establish a functional similarity between fish and mammalian TGF-s, experimental data suggest that fish TGF-s have some functional roles similar to those observed in mammals. TGF-has been observed to influence both reproduction and immune response: in the zebrafish Danio rerio TGF-inhibits gonadotropin-and 17alpha, 20beta-dihydroxyprogesterone-induced oocyte maturation [54]. In the rainbow trout Oncorhincus mykiss, treatment with mammalian TGF-1 significantly inhibits macrophage respiratory burst activity [55] and production of macrophage activating factors by head kidney leucocytes [56].…”
Section: Tgf-mentioning
confidence: 98%